2018
DOI: 10.1371/journal.pone.0199253
|View full text |Cite
|
Sign up to set email alerts
|

Are we choosing the right flagships? The bird species and traits Australians find most attractive

Abstract: Understanding what people like about birds can help target advocacy for bird conservation. However, testing preferences for characteristics of birds is methodologically challenging, with bias difficult to avoid. In this paper we test whether preferred characteristics of birds in general are shared by the individual bird species the same people nominate as being those they consider most attractive. We then compare these results with the birds which appear most frequently in the imagery of conservation advocates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 66 publications
(84 reference statements)
1
35
1
3
Order By: Relevance
“…Here, we demonstrated that traits pertaining to the physical appearance of birds are important in explaining birdwatching scores for birdwatchers and non‐birdwatchers. These results are consistent with previous research showing that people prefer more colourful birds (Garnett et al, ) and birds with patterns in their plumage coloration (Lišková et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Here, we demonstrated that traits pertaining to the physical appearance of birds are important in explaining birdwatching scores for birdwatchers and non‐birdwatchers. These results are consistent with previous research showing that people prefer more colourful birds (Garnett et al, ) and birds with patterns in their plumage coloration (Lišková et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…disservices). For example, forests with larger and denser trees are preferred for their scenic beauty (Ribe, ), while visitors in parks, zoos, and aquaria tend to prefer more colourful animals (Garnett, Ainsworth, & Zander, ; Lišková, Landová, & Frynta, ; Stokes, ), with larger body sizes (Woods, ), and those that are phylogenetically closer to humans (Batt, ). In urban environments, people prefer plants with diverse colours, fragrances and utilities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with some widely held assumptions about citizen science, we found that almost half of the identified projects were deploying structured survey methods, and almost two thirds share their data with national and international biodiversity data repositories. The projects assessed here aim to deepen our understanding of threatened species, the processes that threaten them and raise awareness of the growing biodiversity crisis among Australia's flora and fauna (Garnett, Ainsworth, & Zander, ; Legge et al, ; Woinarski et al, ). Our continental scale assessment has found widespread integration of several key best practice principles among the reviewed citizen science projects for threatened species.…”
Section: Discussionmentioning
confidence: 99%
“…Potensi avitourism dianalisis deskriptif kualitatif-kuantitatif berdasarkan endemisitas, status konservasi, dan keanekaragaman burung [20]. Selain itu juga burung yang berwarna menarik, dan memiliki suara yang merdu [21], burung yang memiliki kicauan indah mengacu pada [22] serta burung jenis raptor [23] berdasarkan [15]. Bersamaan dengan hal tersebut juga terdapat atribut kawasan avitourism [7], dan keanekaragaman jenis tipe pakan burung/feeding guild yang mengacu pada [15].…”
Section: Pendahuluanunclassified
“…Burung yang berwarna menarik, dan memiliki suara yang merdu menjadi daya tarik avitourism [21]. Terdapat enam jenis burung dengan keindahan bulu yang dimiliki yaitu Luntur Harimau, Munguk Loreng, Sepah Hutan, Cekakak Sungai, Ayam hutan Merah, dan Ciu Kunyit (Gambar 5).…”
Section: Gambar 3 Kelimpahan Jenis Burung DI Objek Wisata Girimanikunclassified